Performance Analysis of Wearable Antenna Worn in Close Proximity with Human Body (Journal of Medical Device Technology, 2023)
In the healthcare applications, wearable technology is being rapidly developed. Electromagnetic wave will have an effect when the passive antennas is being closed to the human body because it will act as lossy medium. In this study, the effect of human tissue properties will be studied and will carry out under three conditions: (1) in free space, (2) on human tissue (chest body part) with and without airgap, (3) single and double bended condition of the antenna. The spacing gaps between the antenna and the human chest has been set up such as 2 mm, 4 mm, 6 mm. The bending radiuses for both single and double condition also being set up as 2 mm, 4 mm, 6 mm, 8 mm, 10 mm, and 12 mm. In this study, the effect of human body proximity and human body movement which caused bending to the wearable antenna are also analysed. It will be analysed using the CST Studio Suites 2021 Student Version software
Keywords: Wearable antenna, S11 parameter, Bending